AN ANALYSIS OF FIGURATIVE LANGUAGE IN VIEWS (OPINION COLUMN) OF ONLINE PADANG EKSPRES - Nurhaida Nurhaida; Leni Marlina (Universitas Negeri Padang, 2017)
Language is a media of communication that has an important role in human life. The background of this research because of interesting issues in terms of figurative languages that contained in Online Padang Ekspres Newspaper. The use of these figurative languages sometimes makes the reader difficult to know the meaning of the sentence, because the form of figurative languages cannot be known the meaning literally. This paper aims to identify the type and meaning of figurative language used by the author in Online Padang Ekspres Newspaper in March until May 2016 editions. The paper focuses on the types of figurative language in Opinion Column of Online Padang Ekspres Newspaper, because the writer finds many sentences in form of figurative language in that column. The writer collected data by downloading opinion column of online Padang Ekspres Newspaper. In analyzing the data, the writer groups the data into specific types based on the theory Keraf (2009). Then the writer translated it in English and discussed based on the theory. From the results of this study found as many as 100 words / phrases that categorized into figurative languages. From 100 data, found metaphor as many as 66, 25 phrase belongs to simile, and 9 pieces personification. From these results we conclude that the style of the dominant language used in newspapers Padang Express Online is metaphor and most dominant meaning is positive meaning.